Early Childhood Caries And The Quality Of Life In Children - Dana Cristiana Maxim; Carmen Nicoleta Diana Savin; Radu Cioata; Marinela Pasareanu; Adriana Balan (Romanian Society of Oral Rehabilitation, 2013)
Aim of the study Develop interest and motivate mothers to improve oral health knowledge, producing changes in attitudes and behaviours that will be reflected in the message of education to children; evaluation of risk factors in producing ECC and SECC; examine influences of maternal behaviour and the relation between mother and child based on children's health behaviour. The aim of the study is evaluating the behaviour towards oro-dental health in children and assessing the mothers' level of oral health knowledge and sanogenic attitudes. The target of several oral education programs is to develop habits, attitudes and positive behaviours of oro-dental health. Materials and methods In order to achieve the goals and objectives we realised a longitudinal study on a group of 70 children aged 3.3 to 7.2 years of Iasi city and its suburbs. We have respected the rules of bioethics, of clinical and laboratory investigations performed implicitly in scientific research itself. In the obtained statistical data processing we used SPSS-17 program in Visual Fox Pro 9, statistical tests: ANOVA, Chi-square, Fischer, ROC curve. Results Regarding the frequency of the administration of the bottle, another factor incriminated in producing ECC, it is observed that 48.6% of mothers give a bottle less than 6 times / day / night followed by 14.3% of mothers who give the bottle more than 6 times / day / night and 5.7% of mothers give the bottle all day long. Of all the children in the study did not prevail the number of those artificially fed, and among those who were breastfed, 90% were breastfed from 2 months (8.6%) to 2.9 years old. Conclusions The answers to these questionnaires amply illustrates that, although exists information in both audio and video media as well as in print media, indicating poor level of knowledge is need to implement health education programs, addressing not only to the children, but primarily by addressing parental involvement and especially of motivated and compliance of the mother because the small patient's oral health is shaped, influenced by the level of the knowledge and sanogenic attitudes in the family, especially the mother.